KONSTRUKSI FIKIH ZAKAT DALAM KARYA ULAMA BANJAR DAN RELEVANSINYA DENGAN MANAJEMEN ZAKAT MODERN - Budi Rahmat Hakim (UIN Antasari Banjarmasin, 2020)
This article seeks to identify and describe the construction of zakat thought contained in a number of local works by Banjarese Ulama and to find the relevance of zakat thought as proposed by modern zakat management concepts. The study of the Banjar Ulama's conception of zakat thought was carried out through reading library materials in the form of a number of fiqh works written by Banjar Ulama in the 18-19M century which were also the targets or objects of study. The search results and analysis of the intended local fiqh literature found a number of constructs for discussion of zakat fiqh that discuss the legal provisions of zakat obligations, criteria for zakat objects, zakat distribution mechanisms, the concept of productive zakat, and amil criteria, as well as zakat management authority. From a number of fiqh formulations found, some provisions are still limited conventionally and conservatively, especially regarding the subject of zakat and the criteria for assets which are the object of zakat. While some contain jurisprudence ideas that are relevant to the context of modern management in zakat management, namely related to the productive use of zakat, zakat agency institution with their various duties and functions, and the active role of the government in providing regulatory support and facilitation of operational facilities and infrastructure for zakat management. Some of these fiqh ideas can even be considered as a progressive thought that transcends fiqh thinking in the context of their time.Tulisan ini berupaya mengidentifikasi dan mendeskripsikan konstruksi pemikiran zakat yang terdapat dalam sejumlah karya lokal Ulama Banjar serta menemukan relevansi pemikiran zakat yang dikemukakan dengan konsep manajemen zakat modern. Kajian tentang konsepsi pemikiran zakat Ulama Banjar ini dilakukan melalui penulusuran bahan pustaka berupa sejumlah karya fikih yang ditulis Ulama Banjar dalam rentang abad 18-19M yang sekaligus menjadi sasaran atau objek kajian. Hasil penelusuran dan telaah dari literatur fikih lokal dimaksud menemukan sejumlah konstruk bahasan fikih zakat yang mengulas seputar ketentuan hukum kewajiban zakat, kriteria objek zakat, mekanisme distribusi zakat, konsep zakat produktif, dan kriteria amil, serta otoritas pengelolaan zakat. Dari sejumlah rumusan fikih yang ditemukan tersebut sebagian ketentuannya masih terbatas secara konvensional dan konservatif terutama menyangkut subjek zakat dan kriteria harta yang termasuk objek zakat. Sementara sebagian lagi mengandung gagasan fikih yang relevan dengan konteks manajemen modern dalam pengelolaan zakat, yakni terkait pendayagunaan zakat secara produktif, lembaga keamilan dengan berbagai tugas dan fungsinya, serta peran aktif pemerintah dalam memberikan dukungan regulasi maupun fasilitasi sarana dan prasarana operasional pengelolaan zakat. Beberapa gagasan fikih tersebut bahkan juga dapat dinilai sebagai sebuah pemikiran progresif yang melampaui pemikiran fikih pada konteks zamannya.